Active sites of human MEPE-ASARM regulating bone matrix mineralization. (1st November 2020) - Minamizaki, Tomoko; Sakurai, Kaoru; Hayashi, Ikue; Toshishige, Masaaki; Yoshioka, Hirotaka; Kozai, Katsuyuki; Yoshiko, Yuji
Abstract: The proteolytic fragment ASARM (acidic serine- and aspartate-rich motif) of MEPE (matrix extracellular phosphoglycoprotein) (MEPE-ASARM) may act as an endogenous anti-mineralization factor involved in X-linked hypophosphatemic rickets/osteomalacia (XLH). We synthesized MEPE-ASARM peptides and relevant peptide fragments with or without phosphorylated Ser residues (pSer) to determine the active site(s) of MEPE-ASARM in a rat calvaria cell culture model. None of the synthetic peptides elicited changes in cell death, proliferation or differentiation, but the peptide (pASARM) with three pSer residues inhibited mineralization without causing changes in gene expression of osteoblast markers tested. The anti-mineralization effect was maintained in peptides in which any one of three pSer residues was deleted. Polyclonal antibodies recognizing pASARM but not ASARM abolished the pASARM effect. Deletion of six N-terminal residues but leaving the recognition sites for PHEX (phosphate regulating endopeptidase homolog, X-linked), a membrane endopeptidase responsible for XLH, intact and two C-terminal amino acid residues did not alter the anti-mineralization activity of pASARM. Our results strengthen understanding of the active sites of MEPE-pASARM and allowed us to identify a shorter more stable sequence with fewer pSer residues still exhibiting hypomineralization activity, reducing peptide synthesis cost and increasing reliability for exploring biological and potential therapeutic effects. Highlights: Ser518/520/522 phosphorylation and PHEX cleavage sites in MEPE-ASARM are indispensable for its anti-mineralization effect. MEPE-ASARM does not affect osteogenic proliferation and differentiation. Soluble PHEX cleaved the active site of MEPE-ASARM and attenuated its anti-mineralization effect. Anti-MEPE-pASARM antibodies neutralize the MEPE-pASARM activity in matrix mineralization.